Climate change vulnerability of agroforestry - Neufeldt, Henry; Dawson, Ian K.; Luedeling, Eike; Ajayi, Oluyede C.; Beedy, Tracy; Gebrekirstos, Aster; Jamnadass, Ramni H.; König, K.; Sileshi, Gudeta W.; Simelton, Elisabeth; Sotelo Montes, Carmen; Weber, John C. (World Agroforestry Centre, 2012)
Providing a detailed picture of the values of trees for local people in the tropics is a difficult undertaking. Not only does this represent the difficulty in accounting for values outside formal markets, but it also reflects the multiplicity of the species involved and the many different ways in which trees are used. In these circumstances, one appreach that can be used to gain insight is to focus on a narrower range of species such as tree commodity crops commonly grown by smallhoolders, where more data on economic value are available.